Comparing Public Discourse on Immigration in Scandinavia: Some Background Notes and Preliminary Results - Gripsrud, Jostein (Javnost-The Public, 2019)
This article briefly presents the SCANPUB project, devoted to the comparative study of public discourse on immigration in Scandinavia from 1970 to 2016, from which this issue of Javnost/The Public stems. Its emphasis is on a discussion of the terms “nation” and “nationalism,” particularly the notion of “methodological nationalism” in relation to the project. SCANPUB is not least about how the public sphere in liberal democracies handles large, complex issues over time, and the article thus deals with relatively recent contributions to the theory of the public sphere, concluding with a turn toward deliberative systems theory. Some preliminary empirical results are reported and references are made to the other articles in this issue.